Work, gender roles, and health: neglected mental health issues among female workers in the ready-made garment industry in Bangladesh - Akhter S; Rutherford S; Akhter Kumkum F; Bromwich D; Anwar I; Rahman A; Chu C (Dove Medical Press, 2017)
Sadika Akhter,1,2 Shannon Rutherford,1 Feroza Akhter Kumkum,2 David Bromwich,1 Iqbal Anwar,2 Aminur Rahman,2 Cordia Chu1 1Centre for Environment and Population Health, Griffith University, Brisbane, QLD, Australia; 2International Centre for Diarrhoeal Disease Research Bangladesh, Dhaka, Bangladesh Background: Traditionally, women in Bangladesh stayed at home in their role as daughter, wife, or mother. In the 1980s, economic reforms created a job market for poor, uneducated rural women in the ready-made garment industry, mostly located in urban areas. This increased participation in paid work has changed the gender roles of these women. Women’s earnings support their family, but they are also separated from their children, with impacts on their mental health and well-being. This study explores the lived experience of women in Bangladesh working in the ready-made garment industry as they strive to be mothers and family providers, often in high-stress conditions.Methods: The study was conducted in two industrial areas of Dhaka over 8 months. Data collection included a literature review, 20 in-depth interviews with married female garment workers, and 14 key-informant interviews with officials from the Ministry of Labour and Employment, health-service providers within the garment factories, factory managers, and representatives of the Bangladesh Garment Manufacturers and Exporters Association. The data collected were analyzed thematically.Results: Poverty was a key motivating factor for female migrant workers to move from rural areas. Their children stay in their village with their grandparents, because of their mothers’ work conditions and the lack of childcare. The women reported stress, anxiety, restlessness, and thoughts of suicide, due to the double burden of work and separation from their children and family support. Further, they cannot easily access government hospital services due to their long work hours, and the limited medical services provided in the workplace do not meet their needs.Conclusion: In order to improve the health and well-being of female garment workers, steps should be taken to develop health interventions to meet the needs of this important group of workers who are contributing significantly to the economic development of the country. Keywords: female workers, Bangladesh, ready-made garment industry, gender, health, work